INOVASI JUMPUT SAMPAH ANTI JENTIK (JUMPATIK) DALAM MEWUJUDKAN REJOSARI SEHAT (RESE) - Tri Yuniarti; Toni Prasetyo; Umi Maryam; Isnani Nurhayati; Anggie Pradana Putri (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
One of the health problems in Rejosari Hamlet is about clean and healthy living behavior, especially in terms of solid waste management, as evidenced by the absence of a landfill that is equal to 14.04%. The surrounding community is accustomed to littering, either thrown in rivers, empty gardens, or even thrown in the yard of a house. If left unchecked will cause pollution and malaria. To overcome this, promotive and preventive movements are carried out, specifically regarding waste management. The method used is descriptive qualitative research that describes the real condition of the community with direct observation. The sampling technique is the Total Sampling method. Residents of Rejosari Hamlet welcomed positively and hoped that no one would litter. Residents say that the level of knowledge about clean and healthy behavior is increasing. Increased knowledge and awareness of Dusun residents about clean and healthy living behaviors especially in waste management increased by 45% and residents understood good waste management.